Media Technology and the Academic Performance of the Students. - Jenifer, Tusiimire (Kabale University, 2020)
The research was about media technology and the academic performance of the students at UCC-Kabale. The researcher was guided by the following objectives; to examine the type of media technology used to disseminate information at UCC-Kabale, to establish ways in which media technology improves the academic performance of the students, to examine the challenges hindering he use of media technology towards improving the academic performance of the students and to suggest the ways of enhancing media technology towards improving the academic performance of the students. The questions drawn there in were what are the different types of media technology that are used to disseminate information at UCC-Kabale? What are the ways through which media technology improves the academic performance of the student? What are the challenges facing the use of media technology towards improving the academic performance of the students? What are the ways of enhancing media technology towards improving the academic performance of the students? Respondents who took part in this study totaled to 50 and they were both females and males. They included the students and the staff of which the students took a great part. The information from respondents was collected using questionnaire and interview guides. The data collected about this research topic was analyzed both quantitatively and qualitatively. The study indicates that media technology contributes much towards improving the academic performance of the students implying that there is a positive link between the use of media technology and the academic patterns such as students and the staff of UCC-Kabale. The researcher used tables, figures and percentages were calculated when presenting data collected from field which made it easier to understand and interpret. The study discusses the types of media technology used to disseminate information at UCC-Kabale as print, electronic and broadcasting media. The findings revealed that the use of media technology is being hindered much by over reliance on the media technologies and other challenges like pornography, addictiveness, lack of trained staff and user education among others. Thus this has led to the improper use of media technology towards improving the student’s performance thus poor performance of some students. The research concluded that, UCC students know the importance of media technology because the findings revealed the proper use of all the media technologies available though some few students tend to misuse these media technologies for nonacademic issues. This is because different users perceive the use of media technology differently. The study recommends the acquisition of more print media sources as well as electronic media sources and broadcasting media sources so as to increase the access to information, recruiting of well trained staff, banning of all media which are immoral among others which will help to improve the overall academic performance of the students.